A "transmission gap" between research and practice? A Q-methodology study of perceptions of the application of attachment theory among clinicians working with children and among attachment researchers. Issue 6 (2nd November 2022) - Beckwith, Helen; van IJzendoorn, Marinus; Freeston, Mark; Woolgar, Matt; Stenner, Paul; Duschinsky, Robbie
ABSTRACT: Clinical practitioners are frequently encouraged, through literature, training, and policy, to learn, understand, refer to and use their knowledge of attachment theory and research when working to meet the needs of children and families. However, there has been very little empirical study of how practitioners understand and perceive the relevance of attachment concepts and methods. Q-methodology was used to examine the perceptions of attachment knowledge and its applications for practice among 30 UK clinicians working with children and an international group of 31 attachment researchers. Factor analysis revealed three perspectives, described as: i) pragmatic, developmental, and uncertain, ii) academic, and iii) autodidactic and therapeutic. Participants agreed on core tenants of theory, their aspirations for clinical practice and the inaccessibility of current assessment measures for practitioners. Yet they diverged on their understandings of attachment insecurity, disorganisation, and the implications of both for various aspects of child development.